Vale a pena ver de novo - organização e acesso a arquivos televisivos na França, Grã-Bretanha e no Brasil - Busetto, Áureo (Universidade Estadual Paulista Julio de Mesquita Filho, 2014)
This article presents information about the television audiovisual archiving and the public access to them in France, Great Britain and Brazil. Their comparison and reflection allow us to raise questions and find answers generated both for the preservation of important cultural and historical heritage, as well for the consolidation of citizenship in terms of access to information and its interpretation.

Este artigo informa sobre o arquivamento de audiovisuais televisivos e o acesso público a eles na França, Grã-Bretanha e no Brasil. Sua comparação e reflexão permitem levantar problemas e soluções gerados tanto no âmbito da preservação de importante patrimônio cultural e histórico quanto no desenvolvimento da pesquisa histórica sobre a TV e os seus produtos, bem como a consolidação da cidadania em termos de acesso à informação e sua interpretação.
Worth seeing again - organization and access to television archives in France, Great Britain and Brazil
Keywords: audiovisual televisivo; produção televisiva; arquivo televisivo; história da TV; television audiovisual; television production; television file; TV history